Satisfaction and preferences of the patient visitors toward visiting hour policy in postnatal ward of a selected hospital, Mangalore: A descriptive study - Sonia Karen Liz Sequera; Savitha Pramilda Cutinho; Renita Fernandes; Prerna Kathi; Nimmiya Tom (Wolters Kluwer Medknow Publications, 2019)
Context: Hospital establishes daily visiting hours and rules for the comfort and safety of patients and their loved ones. The need to minimize disruption to the therapeutic environment of the patients while giving patients' and their families' time to be together, is an integral part of patient-centeredness and patient's recovery. Aims: The aim of the study is to determine the level of satisfaction of the patient visitors toward the visiting hour policy, to identify their preferences, and to associate satisfaction toward visiting hour policy with selected demographic variables. Settings and Design: Postnatal ward of selected Medical College Hospital, Mangaluru and a cross-sectional descriptive study design. Materials and Methods: Five-point rating scale to assess the level of satisfaction and a semi-structured questionnaire to identify the preferences of the patient visitors toward visiting hour policy. Statistical Analysis Used: Frequency, mean, standard deviation, mean percentage, and Chi-Square for the association. Results: Majority (74%) were satisfied toward visiting hour policy, and a few (3%) were not satisfied. More than half (59%) visitors prefer the visiting hour policy to be displayed in Kannada language, majority (78%) prefer to have 2-h duration of visiting, and more than half (68%) prefer one visitor at a time. Association was found between satisfaction and experience on previous visits (P = 0.011 < 0.05 level) of the visitors. Conclusions: Pooled results showed that patient visitors were satisfied with visiting hour policy and also had similar preferences for visiting hour policy.